Sustainable urban metabolism - Ferrão, Paulo, 1962-; Fernandez, John, 1963- (The MIT Press, 2013)
A unified framework for analyzing urban sustainability in terms of cities' inflows and outflows of matter and energy. Urbanization and globalization have shaped the last hundred years. These two dominant trends are mutually reinforcing: globalization links countries through the networked communications of urban hubs. The urban population now generates more than eighty percent of global GDP. Cities account for enormous flows of energy and materials--inflows of goods and services and outflows of waste. Thus urban environmental management critically affects global sustainability. In this book, Paulo Ferrao and John Fernandez offer a metabolic perspective on urban sustainability, viewing the city as a metabolism, in terms of its exchanges of matter and energy. Their book provides a roadmap to the strategies and tools needed for a scientifically based framework for analyzing and promoting the sustainability of urban systems. Using the concept of urban metabolism as a unifying framework, Ferrao and Fernandez describe a systems-oriented approach that establishes useful linkages among environmental, economic, social, and technical infrastructure issues. These linkages lead to an integrated information-intensive platform that enables ecologically informed urban planning. After establishing the theoretical background and describing the diversity of contributing disciplines, the authors sample sustainability approaches and tools, offer an extended study of the urban metabolism of Lisbon, and outline the challenges and opportunities in approaching urban sustainability in both developed and developing countries.